PENGARUH IKLIM ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Kridho Hery Gunawan; Khoirun Nissa Febrianti (FEB Universitas Maritim Semarang, 2023)
This research aims to examine the influence of organizational climate and emotional intelligence on employee performance through work motivation as an intervening variable at PT. Indo Bismar Surabaya. The sampling technique used in this study was probability sampling, specifically Simple Random Sampling, with a sample size of 53 employees. Data collection was conducted through interviews and the distribution of questionnaires via Google Forms. The research method was assisted by the Partial Least Squares (PLS) technique using Smart PLS software version 4.0.8.6. The hypothesis testing results indicate the following: There is a non-significant positive influence between organizational climate and employee performance. There is a non-significant positive influence between emotional intelligence and employee performance. There is a significant positive influence between organizational climate and motivation. There is a significant positive influence between emotional intelligence and motivation. There is a significant positive influence between motivation and employee performance. There is a significant positive influence between the organizational climate variable and employee performance through motivation as an intervening variable. There is a significant positive influence between the emotional intelligence variable and employee performance through motivation as an intervening variable.